2017
DOI: 10.3390/nu9121327
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supplementation during Pregnancy and Infancy: Uncertainties and Implications for Research and Policy

Abstract: Iron is particularly important in pregnancy and infancy to meet the high demands for hematopoiesis, growth and development. Much attention has been given to conditions of iron deficiency (ID) and iron deficient anemia (IDA) because of the high global prevalence estimated in these vulnerable life stages. Emerging and preliminary evidence demonstrates, however, a U-shaped risk at both low and high iron status for birth and infant adverse health outcomes including growth, preterm birth, gestational diabetes, gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 58 publications
6
88
0
8
Order By: Relevance
“…Overall, our findings are consistent with those of previous studies demonstrating the potential importance of maternal iron status in fetal programming and lifelong health [3][4][5][6]13,20,25,[55][56][57]. Although a previous review concluded that maternal nutritional status has no effect on offspring neurodevelopmental outcomes, [28] differences in iron status indicators, iron measurements during pregnancy, and the domains assessed [58] could explain some of these inconsistencies. The results of our study also show that in addition to initial iron status, reflected by SF levels, a total intake of iron higher than 14.50 mg/day was associated with higher working memory scores in their children at 7 years, a key executive function that influences other more complex executive functions.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our findings are consistent with those of previous studies demonstrating the potential importance of maternal iron status in fetal programming and lifelong health [3][4][5][6]13,20,25,[55][56][57]. Although a previous review concluded that maternal nutritional status has no effect on offspring neurodevelopmental outcomes, [28] differences in iron status indicators, iron measurements during pregnancy, and the domains assessed [58] could explain some of these inconsistencies. The results of our study also show that in addition to initial iron status, reflected by SF levels, a total intake of iron higher than 14.50 mg/day was associated with higher working memory scores in their children at 7 years, a key executive function that influences other more complex executive functions.…”
Section: Discussionsupporting
confidence: 91%
“…Iron deficiency (ID) in women is a cosmopolitan health and nutritional problem [1]. ID in women is associated with fatigue, impaired muscular performance, decreased ability to maintain body temperature on exposure to cold, mucosal and epithelial abnormalities, pica, disturbances in menstruation [2], adverse pregnancy outcomes [3,4], and decreased mental development of children [5]. The estimated prevalence of ID is lower in women in North America than Africa, Asia, Europe, Latin America and the Caribbean, and Oceania [6], but few cross-sectional studies report the prevalence of ID in women of different race/ethnicity and age who reside in North America [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…29 Interventions aimed at reducing anemia and malnutrition, however, have not always resulted in reduced rates of PTB. [40][41][42][43] Nevertheless, other future interventions may prove beneficial. Finally, we found that women with PTB were less likely to have had an ultrasound.…”
Section: Discussionmentioning
confidence: 99%